Using Demonstration in Teaching Writing through Procedure Text for SMA Students - Sanda, Silfi (Journal of English and Education (JEE), 2009)
This paper is mainly about using demonstration for teaching writing 'by using procedure text in relation to local culture in English language teaching. Recipe of local food is one of the procedure texts that can be applied in teaching writing. The local culture exposed in the text is the local food of Palembang, Pindang, in term of how to make it. How to make Pindang consists of a series of steps which shows how to achieve some goals, called procedure text. In curriculum of SMA, procedure taught as one kind of text materials in English teaching learning process at school. The technique employed for comprehending and appreciating this text is demonstration teaching technique and presenting technique designed especially for motivating students' focus on the text, technique activities for developing students' writing ability.